Developing a Smart Implementation Framework for Blockchain-Based P2P Renewable Energy Trading in Indonesia: A Qualitative Analysis Approach - Ludji, Omrie; Yandri, Erkata; Sidharta, Rendy; Timba, Ayub; Amaral, Clizardo; Aryati, Ratna (Heca Sentra Analitika, 2025)
The shift towards decentralized and sustainable energy frameworks is progressively propelled by innovations in technology and the imperative for energy democratization. Blockchain technology is a viable approach for facilitating peer-to-peer (P2P) energy trading, thereby diminishing dependence on intermediaries while augmenting transparency, security, and efficiency within energy transactions. Nevertheless, the application of blockchain-enabled energy trading continues to be constrained in Indonesia due to regulatory, technical, and economic challenges. This study aims to develop a smart implementation framework for integrating blockchain into P2P renewable energy trading in Indonesia. A qualitative research approach is employed, incorporating content analysis and thematic analysis of policy documents, technical reports, and stakeholder interviews. A blockchain simulation model is also designed to evaluate feasibility, efficiency, and scalability. The findings highlight that blockchain can significantly enhance renewable energy adoption by facilitating direct energy exchanges among prosumers, improving grid resilience, and reducing transaction costs. The proposed framework outlines essential components such as smart contracts, digital tokens, decentralized ledgers, and regulatory compliance mechanisms. Case studies from global implementations, including Power Ledger in Australia and LO3 Energy in the U.S., demonstrate the viability of blockchain-based energy trading. The study concludes that while blockchain has strong potential to transform Indonesia’s energy landscape, successful implementation requires supportive policies, infrastructure investment, and public awareness. Future research should focus on optimizing smart contracts and developing consensus mechanisms tailored to Indonesia’s regulatory and market conditions.